The comprehensive review on the organizational learning and job satisfaction among employees - Dean Nelson Mojolou; Faerozh Madli; Stephen Sondoh Liaison Jr.; Khairunisah Kamsin; Helmina Thomas (Global Academic Excellence, 2025)
Organizational learning and job satisfaction are critical factors influencing employee outcomes and organizational success. Despite their significance, limited research has systematically reviewed how these elements interrelate across workplace contexts. This study aims to bridge this gap by conducting a systematic literature review (SLR) on organizational learning and employee job satisfaction. A structured and transparent review methodology was applied using the PRISMA protocol to ensure rigor and reproducibility. Literature searches were conducted across three major databases, Scopus, ERIC, and EconBiz, identifying 33 primary studies that met the inclusion criteria. The findings were categorized into three major thematic areas: (1) Job Satisfaction, Motivation, and Employee Performance; (2) Organizational Learning, Lifelong Learning, and Professional Development; and (3) Technological Integration and Innovation in Employee Management. The analysis reveals that organizational learning initiatives significantly enhance employee job satisfaction by fostering continuous professional growth, increasing motivation, and improving overall performance. Additionally, integrating technology and innovative management practices is key in promoting dynamic learning environments and sustaining employee engagement. These results highlight the complex but critical interplay between organizational support for learning and the satisfaction levels of employees, suggesting that investment in lifelong learning and innovative technologies is essential for maintaining high performance and retention rates. In conclusion, this SLR underscores the need for organizations to adopt holistic learning strategies and employee-centered management practices to optimize job satisfaction and performance. Future research should further explore the longitudinal effects of technological innovation on organizational learning cultures and employee development over time.